2018
DOI: 10.5455/javar.2018.e247
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of bovine tuberculosis among cattle herds from nomadic peri-urban settlements and cattle slaughtered at the municipal abattoir of Bauchi, North-Eastern Nigeria

Abstract: Objective: This study was designed to determine the prevalence of bovine tuberculosis (bTB) at the municipal abattoir and cattle herds in peri-urban nomadic settlements of Bauchi state of Northeastern Nigeria. Materials and Methods: A total of 2440 cattle slaughtered at the municipal abattoir from June to September were examined for lesions characteristic of bTB and eighty-six (n=86) cows selected from two cattle herds located at temporary nomadic settlements in Bauchi metropolis were also screened for bTB usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…This could be attributed to the fact that female cows are kept for longer period by farmers for breeding purpose than male cattle, and since tuberculosis is a chronic disease, its prevalence had been reported to be higher among adult cattle than the younger ones. The finding was similar to previous reports that tuberculosis was more common among female and adult cattle (Opara et al, 2012;Ejeh et al, 2014c;Kwaghe et al, 2015;Jajere et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…This could be attributed to the fact that female cows are kept for longer period by farmers for breeding purpose than male cattle, and since tuberculosis is a chronic disease, its prevalence had been reported to be higher among adult cattle than the younger ones. The finding was similar to previous reports that tuberculosis was more common among female and adult cattle (Opara et al, 2012;Ejeh et al, 2014c;Kwaghe et al, 2015;Jajere et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…This will ensure not only the production of apparently healthy cattle for human consumption but also affect the socioeconomic status of the herdsmen as well as families that relied on cattle farming as a means of livelihood. In addition, a number of studies have reported that despite the practice of strict prevention and control measures such as meat inspection, surveillance, vaccination, testing of milk for M. bovis , herd testing, and pasteurization of milk, bTB still constitute a major public health problem to humans [ 15 , 33 - 35 ]. In this regard, there is a need for a concerted effort toward the prevention and control of bTB in Bauchi State.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the fluctuation in the occurrence of bTB lesions for the entire study period could be attributed to inadequacies in capacity and lack of thoroughness of the meat inspectors [ 13 , 40 ]. Several studies have reported that the occurrence of bTB in Nigeria is influenced by changes in the climatic condition; this can also contribute to the fluctuation in the yearly occurrence of bTB in that region [ 7 , 35 , 46 ]. Pollock and Neill [ 47 ] also reported that fluctuations in the occurrence of bTB in Northern Nigeria is dependent on seasonal variation.…”
Section: Discussionmentioning
confidence: 99%